"Academic War" over Geography? Death of Human Geography at the Australian National University. Issue 3 (11th December 2018) - Lahiri‐Dutt, Kuntala
Abstract: This article analyses how neoliberal economic policies decide what particular aspects of knowledge are valuable and what are not, and who might be the true holder of that knowledge within the tertiary education system. This assessment leads to some disciplines being seen as less valuable to the system. It argues that the more recent "academic wars" in geography are over the very concept of the university and its role in the contemporary society, what comprises useful knowledge, and who comprises the authoritative figure in the production and distribution of that knowledge. Gender of the geographer therefore becomes a crucial element that determines "authority" in the production of geographical knowledge. To substantiate this argument, the paper takes up the important task of analysing the complex career trajectory of geography within the Australian National University (ANU), the department that was gradually reduced leading eventually to its unfortunate closure in 2009.